Mortality among U.S. military participants at eight aboveground nuclear weapons test series. (3rd April 2022) - Boice, John D.; Cohen, Sarah S.; Mumma, Michael T.; Chen, Heidi; Golden, Ashley P.; Beck, Harold L.; Till, John E.
Abstract: Background: Approximately 235, 000 military personnel participated at one of 230 U.S. atmospheric nuclear weapons tests from 1945 through 1962. At the Nevada Test Site (NTS), the atomic veterans participated in military maneuvers, observed nuclear weapons tests, or provided technical support. At the Pacific Proving Ground (PPG), they served aboard ships or were stationed on islands during or after nuclear weapons tests. Material and methods: Participants at seven test series, previously studied with high-quality dosimetry and personnel records, and the first test at TRINITY formed the cohort of 114, 270 male military participants traced for vital status from 1945 through 2010. Dose reconstructions were based on Nuclear Test Personnel Review records, Department of Defense. Standardized mortality ratios (SMR) and Cox and Poisson regression models were used in the analysis. Results: Most atomic veterans were enlisted men, served in the Navy at the PPG, and were born before 1930. Vital status was determined for 96.8% of the veterans; 60% had died. Enlisted men had significantly high all-causes mortality SMR (1.06); officers had significantly low all-causes mortality SMR (0.71). The pattern of risk over time showed a diminution of the 'healthy soldier effect': the all-causes mortality SMR after 50 years of follow-up was 1.00. The healthy soldier effect for all cancers also diminished over time. The all-cancer SMR was significantly high after 50 years (SMR 1.10) primarily from smoking-related cancers, attributed in part to the availability of cigarettes in military rations. The highest SMR was for mesothelioma (SMR 1.56) which was correlated with asbestos exposure in naval ships. Prostate cancer was significantly high (SMR 1.13). Ischemic heart disease was significantly low (SMR 0.84). Estimated mean doses varied by organ were low; e.g., the mean red bone marrow dose was 6 mGy (maximum 108 mGy). Internal cohort dose–response analyses provided no evidence for increasing trends with radiation dose for leukemia (excluding chronic lymphocytic leukemia (CLL)) [ERR (95% CI) per 100 mGy −0.37 (−1.08, 0.33); n  = 710], CLL, myelodysplastic syndrome, multiple myeloma, ischemic heart disease, or cancers of the lung, prostate, breast, and brain. Conclusion: No statistically significant radiation associations were observed among 114, 270 nuclear weapons test participants followed for up to 65 years. The 95% confidence limits were narrow and excluded mortality risks per unit dose that are two to four times higher than those reported in other investigations. Significantly elevated SMRs were seen for mesothelioma and asbestosis, attributed to asbestos exposure aboard ships.